Productivity Improvement and Cost Reduction in Hydraulic Cylinders - N, Gayathri; N, Karthick; V K, Shanmuganathan; T R, Adhithyan; Kumar T, Madhan; J, Gopalakrishnan (International Journal of Engineering and Technology, 2018)
This paper is aimed to analyze the current status and processes carried out in production of hydraulic cylinders and to optimize the manufacturing methods to increase the production volumes and to reduce the cost of hydraulic cylinders. KAIZEN 10 step methodology is the tool used for improvement. Required data was retrieved from reports, daily logs and job sheets. Then it was analyzed to find bottlenecks in production lines and start working on solutions to improve productivity. Thus fluctuating customer requirements can be met and industries can sustain with competitor entries.Â Â